Artificial Supramolecular Pumps Powered by Light. Issue 43 (2nd June 2021) - Corra, Stefano; Casimiro, Lorenzo; Baroncini, Massimo; Groppi, Jessica; La Rosa, Marcello; Tranfić Bakić, Marina; Silvi, Serena; Credi, Alberto
Abstract: The development of artificial nanoscale motors that can use energy from a source to perform tasks requires systems capable of performing directionally controlled molecular movements and operating away from chemical equilibrium. Here, the design, synthesis and properties of pseudorotaxanes are described, in which a photon input triggers the unidirectional motion of a macrocyclic ring with respect to a non‐symmetric molecular axle. The photoinduced energy ratcheting at the basis of the pumping mechanism is validated by measuring the relevant thermodynamic and kinetic parameters. Owing to the photochemical behavior of the azobenzene moiety embedded in the axle, the pump can repeat its operation cycle autonomously under continuous illumination. NMR spectroscopy was used to observe the dissipative non‐equilibrium state generated in situ by light irradiation. We also show that fine changes in the axle structure lead to an improvement in the performance of the motor. Such results highlight the modularity and versatility of this minimalist pump design, which provides facile access to dynamic systems that operate under photoinduced non‐equilibrium regimes. Abstract : The appropriate integration of molecular recognition and photoswitching phenomena in rotaxane‐type complexes can lead to the realization of artificial supramolecular pumps driven by light. We describe the operation mechanisms of these systems, based on a flashing energy ratchet, is described, and their ability to function autonomously by dissipating light energy away from chemical equilibrium is reported.